Forest owners' attitudes towards the implementationof multi-functional forest management principles inthe district of Suceava, Romania - Liviu Nichiforel (Annals of Forest Research, 2010)
The paper explores the importance of formal and informal institutions in setting attitudes of private owners in respect to responsible forest management. Using a qualitative approach, in form of a case study at the level of Suceava County, the study identifies intrinsic values assigned to the forestland leading to attitudes and motivations in the use of the forest resource. The interviewed forest owners have identified the regulatory framework as highly restrictive having as a result various patterns of behaviours from strict compliance with the rules to illegal activities. Several patterns of self-reported attitudes are discussed in respect to relevant forest owners' typologies and lead to deduced hypotheses about the attitudes and behaviour of Romanian forest owners towards multi-funcionality. The study concludes that, an assessment of the identified patterns at a larger scale are needed as to adapt the financial, regulatory and informational instruments to the diversity of attitudes in respect to multi-functional forest management in small scale forestry.